Morphometric characters of freshwater fish Xenentodon cancila collected from Rajshahi city, Bangladesh (Journal of Bio-Science, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/jbs.v20i0.17739 J. bio-sci.  20:  171-177, 2012